Effect of Ulinastatin Combined With Dexmedetomidine on Postoperative Cognitive Dysfunction in Patients Who Underwent Cardiac Surgery - Zhou, Meiyan; Lyu, Yi; Zhu, Yangzi; Jiang, Teng; Wu, Congyou; Yang, Jianping; Wang, Liwei (Frontiers in Neurology, 2019)
Background Recent studies have shown that early diagnosis and intervention promotes the patient's good prognosis. For patients underwent cardiac surgery who require extracorporeal circulation support, the incidence of postoperative cognitive dysfunction (POCD) is higher than other types of surgery due to greater changes in brain perfusion compared with normal physiological conditions. Recent studies have confirmed that the use of ulinastatin or dexmedetomidine in perioperative period effectively reduces the incidence of POCD. In this study, ulinastatin was combined with dexmedetomidine to assess whether the combination of the two drugs could reduce the incidence of POCD. Methods 180 patients with heart valve replacement surgery undergoing cardiopulmonary bypass from August 2017 to December 2018 were enrolled, with age 60-80 years, ASA grade I-III, education level above elementary school, and either gender. According to the random number table method, patients were grouped into dexmedetomidine + ulinastatin (D+U) group, ulinastatin (U) group, dexmedetomidine (D) group, normal saline (N) control group. Group U was pumped 20000 UI/kg immediately after induction and the first day after surgery, group D continued to pump 0.4 μg/kg/h from induction to 2 hours before extubation, group U+D dexmedetomidine 0.4 μg/kg/h + ulinastatin 20000 UI/kg, and group N equal volume of physiological saline. The patients were enrolled with MMSE before surgery. The cognitive function was assessed by MoCA on the first day before surgery and on the 7th day after surgery. Inflammatory factors such as S100β protein, IL-6, MMP-9, and TNF-α were detected in peripheral blood before anesthesia (T0), immediately after surgery (T1), and immediately after extubation (T2). Results 154 patients enrolled in this study. Compared with group N, the incidence of POCD in group U+D was the lowest (P<0.05), followed by group U and group D. Group U+D had the lowest concentration of inflammatory factors at the T1 and T2 time points, followed by group U and group D. Conclusions Both ulinastatin and dexmedetomidine can reduce the perioperative inflammatory response and the incidence of POCD in patients with heart valve surgery, and the combination of them can better reduce the incidence of POCD.